Modern transformations of Kyiv public spaces: prerequisites, manifestation and specifications - Мезенцев, Костянтин; Мезенцева, Наталія (Human Geography Journal, 2017)
In different historical periods the role of different functions of urban public spaces inUkraine(political, communication, entertainment, shopping, recreational, territorial identity and self-identification, etc.) has changed. Now public spaces ofUkraine’s cities and especially of Kyiv are characterised by overlapping of universal and specific transformations. This paper examines the causes, positive and negative effects of commercialisation and privatisation of public spaces, their separation, "closure", "Disneyfication", "Europeanisation", virtualisation, sacralisation, the growing role of malls as public spaces. We focused on the analysis of preconditions for urban public spaces transformation in post-Soviet space, identification of specific trends and prospects of their possible changes. In this regard, Kyiv is a good case as former Soviet city where various factors lead to distinct expression of both traditional and specific transformations in time and space. The paper presents the results of a questionnaire survey of the Kyiv’s students in2014 inorder to understand the importance and frequency of usage of different types of public spaces. We found that the role of malls as public space for leisure and communication increases, but there is a difference of opinion on the value of malls as public spaces for local students and those who came from other regions.